The interaction of actual and fundamental house prices: A general model with an application to Denmark and Sweden - Peter Birch Sørensen; U. Michael Bergman (University of Copenhagen, Economic Policy Research Unit (EPRU), 2016)
The paper presents a general method for estimating a country's level of fundamental house prices and its interaction with actual house prices. We set up a unified empirical model which can be used to analyze the time-series behavior of the fundamental house price and to test various hypotheses regarding its relation to the actual house price. To illustrate how the method works, we apply it to data for Denmark and Sweden. We find a tendency for actual house prices to converge on fundamental prices, albeit rather slowly.
Keywords: R31; G12; C31; 330; fundamental house prices; house price dynamics; housing bubbles